ANALYSIS OF THE DYNAMICS OF HARMFUL RELEASE TO THE ENVIRONMENT IN TERMS OF TIME - Draganov, B. (Енергетика і автоматика, 2016)
The characteristic of harmful emissions into the environment. Attention is paid to the aerosol particles of radioactive components. It specifies the role of the ambient temperature on the man-made emissions, and Biofactors. The analysis of patterns of change in emissions in the time aspect.